Expansionary fiscal consolidation under sovereign risk - Carlos Esquivel; Agustin Samano (Rutgers University, Department of Economics, 2024)
We study how debt limits can be expansionary in economies facing sovereign risk. We develop a sovereign debt model with capital accumulation, long-term debt, and fiscal rules that features two distortions: debt dilution and a pecuniary externality of private investment on spreads. The optimal debt limit increases capital accumulation due to lower sovereign risk, generating an economic expansion in the long run. Welfare gains are a result of lower sovereign spreads due to expectations about future borrowing and investment. We present evidence of a positive (negative) relation between debt limits and investment (spreads), consistent with the predictions of the model.
Keywords: F34; F41; 330; Fiscal rules; Sovereign debt; Expansionary fiscal consolidation